2002
DOI: 10.1302/0301-620x.84b5.12276
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial total wrist replacement in patients with rheumatoid arthritis

Abstract: We have implanted 76 biaxial total wrist prostheses as a primary procedure in patients with rheumatoid arthritis of the wrist. A total of 66 was reviewed at a mean follow-up time of 52 months. Pain was relieved in 67% of the surviving wrist replacements. On the basis of the Hospital for Special Surgery scoring system, 49 wrists (74%) were graded as fair to excellent. More than half of the 27 patients who had an arthrodesis on the contralateral wrist would have preferred a second arthroplasty. Five replacements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 15 publications
2
26
0
8
Order By: Relevance
“…Five of the replacements were revised or fused because of loosening, and an additional 9 showed radiographic signs of loosening [25]. Another short-term study of 16 Biax wrists showed good-to-excellent results in 69% at a mean 25-month follow-up.…”
Section: Resultsmentioning
confidence: 97%
“…Five of the replacements were revised or fused because of loosening, and an additional 9 showed radiographic signs of loosening [25]. Another short-term study of 16 Biax wrists showed good-to-excellent results in 69% at a mean 25-month follow-up.…”
Section: Resultsmentioning
confidence: 97%
“…TWA is an established alternative that preserves some motion and improves patient satisfaction. Particularly in patients with bilateral disease, patients with a TWA on one side and arthrodesis on the other preferred the side with the arthroplasty [13]. However, historically TWA has been associated with a high number of complications and concerns regarding survivorship [1,4,6,7,[9][10][11][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Total wrist arthroplasty has also been found to be unsuitable for severe joint malformation, chronic subluxion, and collapse of the carpal bone. 6 It is clear that optimum treatments are required for each stage of RA joint destruction.…”
Section: Introductionmentioning
confidence: 99%